DINAMIKA HUBUNGAN DIPLOMATIK TURKI DAN RUSIA PASCA PENEMBAKAN PESAWAT SUKHOI 24 - Hatta Zailiyus; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This Research analyzes Diplomatic Relations Dynamic About Turkey and Russia after the incident of Aircraft. The bilateral relations that is held by the two countrys are unlikely to have no problem in them , the relationship must have been tidal and subsiding. Among the two countries that run this bilateral relationship one of them must be the big country that dominations the power in this relationship. The problems that aircraft airline in that sukhoi 24, will be discussed by the author throught a case study of shootingof Russianmilitary aircraft by turkey which cause the Russian ignited its anger and cause the state of bilateral diplomatic one of them. And relation between the two countries threatened its substainability, after this incident, the Russian issued diplomatic came out after existence of the political influed behind.In this Journal the authors will analyze the policy diplomatic with the science of International Relations and analyze how the purpose of Russia issued the policy for Turkey. Key word : Russia, Aircraft Shooting, Sukhoi 24, Diplomatic Relation,, Turkey